Find all solutions by factoring. \( 2 a^{2}-5 a=3 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To start, let's rearrange the equation into standard form. We need to move everything to one side: \( 2a^2 - 5a - 3 = 0 \). Next, we will factor this quadratic equation. To do that, we look for two numbers that multiply to \( (2)(-3) = -6 \) and add up to \(-5\). The numbers \(-6\) and \(1\) fit the bill, so we can rewrite the middle term: \( 2a^2 - 6a + a - 3 = 0 \). Now, we group our terms: \( (2a^2 - 6a) + (a - 3) = 0 \). Factoring each group we get: \( 2a(a - 3) + 1(a - 3) = 0 \). Now we notice that \( (a - 3) \) is a common factor: \( (2a + 1)(a - 3) = 0 \). Setting each factor equal to zero gives us our solutions: 1. \( 2a + 1 = 0 \) which simplifies to \( a = -\frac{1}{2} \). 2. \( a - 3 = 0 \) which gives \( a = 3 \). The solutions to the equation \( 2a^2 - 5a = 3 \) are \( a = -\frac{1}{2} \) and \( a = 3 \).